Oral History Program Interview Elbert Ray Garretson - Garretson, Elbert Ray
Born in Chattanooga, Chomanche County, Oklahoma, on November 15, 1915, Garretson brought his family to Kern County, California in 1936. Garretson comments on the New Deal policies, home remedies used, his life as a minister, the lives of people in the migrant camps, and why the term "Okie" never really bothered him.